Telmisartan and Rosuvastatin Synergistically Ameliorate Dementia and Cognitive Impairment in Older Hypertensive Patients With Apolipoprotein E Genotype - Hu, Wenjing; Li, Ying; Zhao, Yingxin; Dong, Yuanli; Cui, Yi; Sun, Shangwen; Gong, Gary; Zhang, Hua; Chai, Qiang; Wang, Juan; Liu, Zhendong (Frontiers in Aging Neuroscience, 2020)
Objective: To investigate the effect of telmisartan, rosuvastatin, or their combination on dementia and to understand the impact of Apolipoprotein E (APOE) genotype on the effect of the medications in older patients with hypertension. Methods: This is a double-blind, randomized, and placebo-controlled trial using a 2-by-2 factorial design. Between April 2008 and November 2010, 1244 hypertensive patients aged ≥60 years without cognitive impairment were recruited from communities in six cities in Shandong area, China. Patients were randomized into telmisartan and rosuvastatin administration after a 2-week washout period. APOE genotype was identified at the baseline. Possible dementia was determined using the combination of the global cognitive function and Assessment of the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE). Results: Over an average follow-up of 7 (IQR: 6.7–7.2) years, telmisartan and rosuvastatin significantly reduced the cognitive impairment progression and the incidence of dementia. There was a synergistic interaction between telmisartan and rosuvastatin to reduce the cognitive impairment and the incidence of dementia (Padjusted <0.001). The cognitive impairment progression and the risk of dementia were higher in the hypertensive patients with APOE ε4 allele than in those without APOE ε4 allele. Rosuvastatin medication significantly alleviated the cognitive impairment progression and the risks of dementia in patients with APOE ε4 allele. Conclusion: The combination of telmisartan and rosuvastatin might be an effective prevention and/or treatment strategy for cognitive impairment and dementia, especially in the hypertensive patients with APOE ε4 allele.